Bentuk Pertunjukan dan Teknik Penokohan Teater Rakyat Kuda Gipang Carita - Bayu Bastari Setiawan (Program Studi Pendidikan Seni Pertunjukan FKIP ULM, 2016)
AbstractResearch takes place on Sanjaya Raden Group, Parigi Village, Tapin District, South Kalimantan is focused to determine the form of performances and characterization techniques in the art of theater Kuda Gipang Carita. This research use approach (method): qualitative-descriptive. Data collection techniques include, observation, documentation, interview, and literature. The results of this study mentions that the Kuda Gepang Carita is a folk theater art forms of South Kalimantan royal palace-centric show. Form of presentation has a structure that contains six sections: mangibar, trial kingdom, scenes, climax and cover. Regarding the characterization technique determined by the accuracy of the figures according to its function in the story.Keywords: kuda gipang carita, folk theater, forms of performance